Использование КНИ-транзистора в качестве генератора колебаний напряжения - Ninidze, G. K.; Pavljuk, S. P.; Ishchuk, L. V.; Kushnirenko, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Voltage and current oscillations in field-effect transistors fabricated using silicon-on-insulator (SOI) technology have been investigated. It has been shown that by changing the transistor’s supply conditions, the oscillation frequency can be varied over a wide range (0.1–1 MHz), as well as their nature — from quasi-harmonic to relaxation oscillations. This makes it possible to use such a transistor as a voltage oscillation generator. It was established that these oscillations are caused by physical processes occurring directly within the transistor. A qualitative description of these processes is provided.